BS44 Cytokine induced downregulation of plasma membrane calcium atpase 4 gene increases sensitivity to apoptosis in pulmonary artery endothelial cells. (May 2019) - Ihugba, Jude; Kurusamy, Satishkumar; Ranjit Immanuel, Reshma Naomi; Khan, Kinza; Jayachandran, Jayashree; Arnold, Nadine; Polla, Priscille; Gomez-del Arco, Pablo; Redondo, Juan Miguel; Cotton, James; Upton, Paul D; Morrell, Nicholas; et al.
Abstract : Introduction: Pulmonary arterial hypertension (PAH) is a life-threatening disease characterized by progressive vasoconstriction, vascular remodelling, and occlusion of small pulmonary arteries. It leads to increased pulmonary resistance and finally right ventricular failure. The disorder has no cure and current therapies only target vasoconstriction but have little effect on vessel remodelling. Increased activity of pro-inflammatory cytokines is linked to PAH pathogenesis. In this study, we analysed the effect of TNF-alpha and IL-1Betaβon the expression of Plasma Membrane Calcium ATPase 4 (PMCA4) in pulmonary artery endothelial cells (PAEC). Methods: PAEC were cultured for different times and with different doses of TNF-alpha or IL-1Beta. Expression of PMCA4 RNA and protein was determined by qPCR and western blot respectively. PMCA4 expression was silenced using siRNA specific for human PMCA4. Quantification of apoptotic cells was performed by flow cytometry and TUNNEL. Results: Treatment of PAEC with TNF-alpha or IL-1Beta induced a time- and dose-dependent decrease in the levels of RNA for PMCA4. Analysis of PMCA4 RNA levels in the lungs of mice with overexpression of ectopic TNF-alpha confirmed the in vivo relevance of these observations. RNA decay experiments performed by blocking cellular transcription with Actinomycin D indicate that the downregulation of PMCA4 RNA levels mediated by pro-inflammatory stimuli in PAEC is the result of a decrease in RNA stability. In agreement with the reduction observed in RNA levels, PMCA4 protein expression was strongly decreased by treating PAEC with TNF-alpha or IL-1Beta. Silencing PMCA4 gene expression sensitised PAEC to apoptosis, suggesting that PMCA4 protects PAEC to apoptosis induced by pro-inflammatory cytokines. Conclusion: The pro-inflammatory cytokines TNF-alpha and IL-1Beta significantly downregulate the expression of the PMCA4 gene in PAEC at the RNA and protein level. Decrease in PMCA4 expression sensitised PAEC to apoptosis. This indicates that the PMCA 4 gene might play an important role in the apoptotic loss of endothelial cells observed in the pulmonary arterioles of patients with PAH. Conflict of interest: None